A SWOT Analysis for a Roadmap towards Sustainable Electric Power Generation. (20th July 2022) - Shaikh, Asadullah; Hameed Shaikh, Pervez; Kumar, Laveet; Husain Mirjat, Nayyar; Ahmed Memon, Zubair; El Haj Assad, Mamdouh; Alayi, Reza; Eskandarpoor, Behrouz
Abstract : During the last decade, the abundance of wind, solar, and conventional energy sources have been widely utilized in Sindh, Pakistan, to meet the energy demand-supply gap of the country. Some of these energy projects have been approved, are under constructional and operational phases and have connected to the National grid successfully. However, these energy sources are being influenced by several constraints, which keep the project developmental phases away from their technological upgradation. Therefore, the aim of the present study is to perform a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis of existing energy projects in Sindh to examine its current conditions and future roadmap to promote its valuable utilization. The outcomes of the study have identified several socio-economic and environmental impacts on the sustainable development of renewable energy sources. The study concludes that energy strategic policy must contain financial profits, energy security, and environmental protection. This SWOT study will encourage local and foreign investors, researchers, and engineers to invest their financial and technical abilities towards Sindh to get benefit from the hub of energy sources. They can initiate independent power generation and distribution companies on stated sites and can provide cost-effective tariffs from green energy sources with more revenue and less payback period. It can ultimately increase profitable business as well as can boost the state's economy efficiently.